Arthroscopic or Open Excision of Intraarticular Osteoid Osteoma in the Elbow Joint – a Case Report - Hainzer, Lisa; Reichkendler, Markus; Weitlaner, Helmut; Pauly, Stephan; Gerhardt, Christian; Rau, Daniel; Thiele, Kathi (Zeitschrift für Orthopädie und Unfallchirurgie, 2025)
Pain and stiffness are common symptoms that occur in many elbow pathologies. In the diagnostic algorithm for non-specific elbow pain, benign tumour lesions should be ruled out in rare cases. The following case presentations demonstrate that rare entities such as osteoid osteoma (OO) can be the cause for unclear elbow complaints.Three male patients presented with non-traumatic elbow pain over several months before seeking medical help for the first time. Their main concern was restricted Range of Motion (ROM). The plain radiographs were normal in ⅔ cases, and the CT-scans showed unspecific signs of free joint bodies in the area of the incisura trochlearis of the proximal ulna in the initial stages. Either arthroscopic or open excision was performed as based on CT and/or MRI scans. The decision on the appropriate approach of treatment depends on the localisation of the OO. In particular, the medial ulnohumeral joint section cannot be completely visualised and remains reserved for the open procedure, with the associated disadvantages. Histopathological preparation confirmed the diagnosis. Overall, both techniques seem to reduce the patient’s pain immediately, restore ROM with a slight delay, and show almost no recurrence rates of the tumorous lesions.Patients presented with elbow pain and restricted ROM with no history of elbow trauma; plain radiographs as well as nocturnal pain are highly indicative of OO. Even though this is rare, we should always keep it in mind in order to protect the patient from wrong or delayed diagnosis and treatment. A surgical approach is to be preferred, particularly in the case of intra-articular localisation.
Keywords: elbow; osteoid osteoma; elbow pain; stiffness; elbow arthroscopy